Emergence of CXCR4-tropic HIV-1 variants followed by rapid disease progression in hemophiliac slow progressors. - Tsunefusa Hayashida (PLoS ONE, 2017)
The association between emergence of CXCR4-tropic HIV-1 variants (X4 variants) and disease progression of HIV-1 infection has been reported. However, it is not known whether the emergence of X4 variants is the cause or result of HIV-1 disease progression. We tried to answer this question.HIV-1 env sequences around the V3 region were analyzed in serially stocked samples in order to determine whether X4 variants emerged before or after the fall in CD4+ T-cell count.The study subjects were five HIV-1-infected hemophiliac slow progressors. Deep sequencing around the HIV-1 env V3 region was conducted in duplicate. Tropism was predicted by geno2pheno [coreceptor] 2.5 with cutoff value of false positive ratio at <5%. When X4 variant was identified in the latest stocked sample before the introduction of antiretroviral therapy, we checked viral genotype in previously stocked samples to determine the time of emergence of X4 variants.Emergence of X4 variants was noted in two of the five patients when their CD4+ T-cell counts were still high. The rate of decrease of CD4+ T-cell count or of rise of HIV-1 load accelerated significantly after the emergence of X4 variants in these two cases. Phylogenetic analysis showed that these X4 variants emerged from CCR5-tropic HIV-1 viruses with several amino acid changes in the V3 region.The emergence of X4 variants preceded HIV-1 disease progression in two hemophiliac slow progressors.